MRI findings of intracranial primary CNS lymphoma in immunocompetent patients: a Malaysian tertiary hospital experience - Ab Rahman, Siti Soraya; Muda, Ahmad Sobri (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: The present study aimed to characterize the MRI features of intracranial primary central nervous system lymphoma (PCNSL) in the Malaysian population, and to compare the findings with other population-based studies. Methods: Twenty-four patients with histologically confirmed PCNSL from 2008 to 2014 were identified. Eighteen patients had MRI images at presentation available for review. The images were reviewed by two radiologists, noting the number, size, location, signal characteristics, perilesional oedema and characteristics of enhancement of the lesions. Results: Ten patients had solitary lesions, while 8 patients had multiple lesions with a total of 31 lesions. The lesions were mostly located in the frontal lobe and basal ganglia. Most lesions were hypointense on T1 sequences, hyperintense on T2 sequences, with moderate to marked perilesional oedema. All lesions showed contrast enhancement. Five lesions demonstrated the ‘notch sign’, 1 lesion showed ‘open-ring’ pattern of enhancement and 1 lesion had a non-enhancing core. Seventeen lesions demonstrated an uneven enhancement pattern, mainly in lesions that are abutting the ventricular margins. Conclusion: MRI findings of patients with PCNSL in our population concur with other population-based studies. Enhancement patterns like the ‘notch sign’, ‘open-ring’, and uneven enhancement are not uncommon in PCNSL.